The Conjugation Stress of Ligand via Metal Core as the Cause of Changes in the Reactivity of Coordinated 1-Hetero-1,3-Dienes - A.I. Kuramshin; E.V. Kolpakova; R.A. Cherkasov; V.I. Galkin (Учёные записки Казанского университета: Серия Естественные науки)
Using quantum-chemical calculations carried out for interpretation of the experimentally discovered reactivity of 1-hetero-1,3-dienes that are mono- and bidentally coordinated with the transition metal core, we have revealed that the difference in hydrophosphorylation directions of the free organic molecule and the same molecule involved in the coordination sphere of the transition metal can be explained by either weakening or complete loss of conjugation between the C=C and C=X fragments as a result of coordination. In the case of monodentate coordination of heterodiene with the transition metal according to the eta(2)(C,C)-type, the conjugation weakening is suggested to be maximum for the transition metal characterized by the minimum electronegativity, which predetermines the increased contribution of the metalcyclopropane resonance structure into the general bonding mode. Organometallic compounds having the heterodiene ligand bidentally coordinated demonstrate the conjugation weakening parallel to the metal radius.